2014
DOI: 10.1038/cddis.2014.78
|View full text |Cite
|
Sign up to set email alerts
|

Blocks to thyroid cancer cell apoptosis can be overcome by inhibition of the MAPK and PI3K/AKT pathways

Abstract: Current treatment for recurrent and aggressive/anaplastic thyroid cancers is ineffective. Novel targeted therapies aimed at the inhibition of the mutated oncoprotein BRAFV600E have shown promise in vivo and in vitro but do not result in cellular apoptosis. TNF-related apoptosis-inducing ligand (TRAIL) induces apoptosis in a tumor-selective manner by activating the extrinsic apoptotic pathway. Here, we show that a TRAIL-R2 agonist antibody, lexatumumab, induces apoptosis effectively in some thyroid cancer cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 50 publications
3
26
0
Order By: Relevance
“…The MAPK signaling pathway plays an important role in regulating apoptosis induced by various cellular stresses and chemotherapeutic agents [45]. However, the detailed mechanisms of these pathways in cell death remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK signaling pathway plays an important role in regulating apoptosis induced by various cellular stresses and chemotherapeutic agents [45]. However, the detailed mechanisms of these pathways in cell death remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3K/Akt signaling pathway is also responsible for modulating multiple processes in thyroid cancer cells [29]. For instance, down-regulation of PI3K and Akt phosphorylation inhibits thyroid cancer cell proliferation, invasion, and apoptosis [30,31]. Thus, we detected the PI3K/Akt signaling pathway proteins to reveal the molecular mechanisms of CA4-activated thyroid cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, 81.3% of ATC have been found to carry genetic alterations that could activate both pathways [32]. Recent studies have shown that blocking these two essential pathways in aggressive thyroid cancer cells allow for their sensitization to novel targeted therapies and traditional chemotherapeutic compounds [37, 20]. …”
Section: Pi3k Signaling Pathwaymentioning
confidence: 99%